Method for repairing positive electrode of liquid leakage type waste lithium iron phosphate power battery
Through the lithium citrate repair method, the problems of high energy consumption in lithium-ion battery recycling and low positive electrode recycling efficiency of liquid-leaking waste lithium iron phosphate batteries are solved, and the repair of positive electrode materials with simple process, low energy consumption and high efficiency is achieved, which improves the repair of positive electrode materials with simple process, low energy consumption and high efficiency. Discharge capability and structural integrity of the material.
Patent Information
- Application Number
- CN202411292027.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-ion battery recycling methods have problems such as high energy consumption and the use of strong acids and alkalis. There are few researches on the recycling of the positive electrode of the liquid-leaved waste lithium iron phosphate battery, resulting in its low discharge specific capacity and failure to effectively recover.
Lithium citrate is used as the lithium source and reducing agent, and through deep discharge, removal of residual electrolyte, high-temperature annealing, separation of powder, calcination and other steps, the leakage-type waste lithium iron phosphate positive electrode material is repaired to achieve the restoration of its structure and components.
The liquid-leaking waste lithium iron phosphate positive electrode has been repaired with short process cycle, low energy consumption and high recycling efficiency, which improves the discharge specific capacity and structural integrity of the material, and has economic and universal advantages.
Smart Images

Figure CN119153832A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and more particularly to a method for repairing positive electrodes of leaking waste lithium iron phosphate power batteries. Background Art
[0002] Lithium iron phosphate (LiFePO4, LFP) batteries have attracted much attention due to their high safety performance, long service life, module-free design and other emerging technological breakthroughs, and are widely used in electric vehicles and energy storage power stations. With the explosive growth of new energy vehicles in recent years, the scrap volume of retired lithium-ion batteries has also increased day by day. The current recycling methods of lithium-ion batteries, including pyrometallurgical and wet recycling, have problems such as high energy consumption and the use of strong acid and alkali reagents.
[0003] Therefore, the main idea currently explored by researchers is to restore the composition and structure of the failed positive electrode material to its original state without destroying the structure of the electrode material, thereby achieving the optimal sustainable recycling of waste lithium-ion batteries.
[0004] The waste lithium iron phosphate cathode material currently used in various reports still has a high discharge capacity (80-100 mAh g -1 ), but little research has been done on the recovery of positive electrodes from leaking waste LFP batteries. The discharge capacity of the LFP positive electrode material in such waste LFP batteries is low due to leakage, even as low as 30 mAh g -1 , the lithium content in the inductive coupling test (ICP) is only 1%. Summary of the invention
[0005] In view of this, the present invention provides a method for directly recovering the positive electrode of leaking waste lithium iron phosphate power batteries by using lithium citrate, which has the advantages of simple process, short process cycle, low energy consumption and high recovery efficiency.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for repairing the positive electrode of a leaking waste lithium iron phosphate power battery comprises the following steps:
[0008] (1) Place the leaky waste lithium iron phosphate power battery in a salt solution and allow it to stand for deep discharge;
[0009] (2) disassembling the discharged battery to obtain a discarded lithium iron phosphate positive electrode sheet, a separator and a discarded graphite negative electrode;
[0010] (3) soaking the obtained waste lithium iron phosphate pole piece in dimethyl carbonate to remove residual electrolyte, and then drying to remove residual dimethyl carbonate to obtain a dried waste lithium iron phosphate pole piece;
[0011] (4) subjecting the obtained waste lithium iron phosphate electrode to high temperature annealing to remove the binder and residual organic matter thereon;
[0012] (5) separating the aluminum foil and the positive electrode powder from the lithium iron phosphate electrode after high temperature annealing, and obtaining the waste lithium iron phosphate positive electrode powder after separation;
[0013] (6) dispersing the waste lithium iron phosphate positive electrode powder and the lithium citrate reagent into deionized water, and evaporating the deionized water to obtain a uniformly dispersed powder;
[0014] (7) The obtained powder is placed in a furnace and calcined to obtain a repaired lithium iron phosphate positive electrode.
[0015] Preferably, the salt solution in step (1) is allowed to stand for 24 hours in a saturated sodium chloride solution.
[0016] Preferably, the disassembly in step (2) is carried out in a glove box filled with argon.
[0017] Preferably, the soaking time in step (3) is 12 hours; and the drying is performed at 80° C. for 12 hours.
[0018] Preferably, the high temperature annealing in step (4) is to increase the temperature to 500° C. at a heating rate of 5° C. / min in an argon atmosphere and keep the temperature for 5 hours.
[0019] Preferably, the waste lithium iron phosphate positive electrode powder and the lithium citrate reagent in step (6) are weighed according to Li:Fe:P=1.04:1:1.
[0020] Preferably, the calcination in step (7) is carried out by heating the temperature to 750° C. at a heating rate of 5° C. / min in an argon atmosphere and keeping the temperature for 10 hours.
[0021] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. Traditional positive electrode material recycling methods such as wet recycling and pyrometallurgical recycling are not applicable to lithium iron phosphate positive electrode materials that only contain lithium and have recycling value. Direct recycling has more economic advantages.
[0023] 2. The ordinary direct recycling method is aimed at the waste lithium iron phosphate positive electrodes with light damage, while this scheme is aimed at the waste lithium iron phosphate positive electrodes with serious damage. Due to the unique "low-temperature carbon coating + high-temperature lithium supplementation" characteristics of lithium citrate, this repair scheme is more universal.
[0024] 3. In this work, lithium citrate is used as a lithium source and reducing agent. This lithium salt decomposes into amorphous carbon and lithium carbonate at a lower temperature, and further decomposes into lithium oxide at a higher temperature, thus achieving the dual effects of "low-temperature carbon packaging + high-temperature lithium supplementation". BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0026] Figure 1 This is a SEM image of the positive electrode of the leaking waste lithium iron phosphate power battery recovered in Example 1 of the present invention.
[0027] Figure 2 This is a SEM image of the positive electrode of the leaking waste lithium iron phosphate power battery after repair in Example 2 of the present invention.
[0028] Figure 3 This is an XRD comparison diagram of the positive electrode of the leaking waste lithium iron phosphate power battery recovered in Example 3 of the present invention.
[0029] Figure 4 This is a charge and discharge performance diagram of the lithium iron phosphate half-cell assembled in Example 3, Example 4, and Example 6 of the present invention at a rate of 0.2C. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] This embodiment provides a method for separating a positive electrode material of a leaky waste lithium iron phosphate power battery from an aluminum foil, comprising the following steps:
[0033] (1) The leaky waste lithium iron phosphate power battery is placed in a saturated sodium chloride solution and allowed to stand for 24 hours to obtain a deeply discharged waste lithium iron phosphate battery.
[0034] (2) placing it in a glove box filled with argon gas for disassembly to obtain discarded lithium iron phosphate positive electrode sheets, diaphragms and discarded graphite negative electrodes.
[0035] (3) The obtained leaking waste lithium iron phosphate power battery lithium iron phosphate pole piece is soaked in dimethyl carbonate (DMC) for 12 hours to remove the residual electrolyte, placed in a vacuum oven, and allowed to stand at 60°C for 12 hours to remove the residual dimethyl carbonate, thereby obtaining the dried waste lithium iron phosphate pole piece. The obtained waste lithium iron phosphate pole piece is placed in a tubular furnace, and the temperature is raised to 500°C at a heating rate of 5°C / min in an atmosphere of 95% argon / 5% hydrogen, and kept warm for 5 hours to remove the binder and residual organic matter thereon. The lithium iron phosphate pole piece after high temperature annealing is separated from the aluminum foil and the positive electrode powder by vibrating screening, and the waste lithium iron phosphate positive electrode powder is obtained after separation.
[0036] (4) Grind the obtained powder and pass it through a 200-mesh sieve to obtain the final product S-LFP.
[0037] XRD test is performed on waste lithium iron phosphate positive electrode materials, such as Figure 3 As shown in , XRD shows relatively messy characteristic peaks, indicating that there are a large number of impurities such as FePO4, Li3Fe2(PO4)3, etc. in S-LFP, and it is quite different from the standard lithium iron phosphate PDF card.
[0038] SEM test of waste lithium iron phosphate cathode materials, such as Figure 1 As shown in the SEM image, the structure of the leaking waste lithium iron phosphate is severely damaged, the grain size is uneven, and there is agglomeration.
[0039] Example 2
[0040] This embodiment 2 provides a method for directly repairing the positive electrode of a leaking waste lithium iron phosphate power battery.
[0041] The waste lithium iron phosphate positive electrode powder and lithium citrate reagent obtained in Example 1 were weighed and dispersed in deionized water according to Li:Fe:P=1.04:1:1, and the deionized water was evaporated to obtain a uniformly dispersed powder. The dried powder was heated to 750°C at a heating rate of 5°C / min in an atmosphere of 95% argon / 5% hydrogen, and kept warm for 10 hours to obtain the repaired lithium iron phosphate material R-LFP.
[0042] XRD test was performed on R-LFP, such as Figure 3 As shown in , the characteristic peak of lithium iron phosphate in XRD is obvious, and the intensity of the diffraction peak is greatly improved, which is highly consistent with the peak position of the standard lithium iron phosphate PDF card, indicating that the lattice of the leaking waste lithium iron phosphate has been completely repaired after repair.
[0043] SEM test of R-LFP, such as Figure 2 As shown in the SEM image, the lattice structure of lithium iron phosphate has been restored after repair, a carbon layer is coated on the surface, and the grain size is uniform.
[0044] Example 3
[0045] The leaky waste lithium iron phosphate positive electrode material powder obtained in Example 1 was mixed with a conductive agent (Super P) and a binder (PVDF) in a ratio of 8:1:1 and ground for 30 minutes, then N-methylpyrrolidone (NMP) solution was added and continued to grind to form a uniform slurry, and then the mixed slurry was scraped on an aluminum foil and dried in an oven at 80°C for 12 hours to obtain S-LFP to prepare a positive electrode sheet. Then, S-LFP was used as the positive electrode, lithium foil as the negative electrode, and PP film as the separator to assemble a button battery. 20 μL of electrolyte was dripped on both sides of the positive and negative electrodes, and the assembled battery was left to stand for 8 hours before electrochemical testing.
[0046] The test was carried out at a charge and discharge rate of 0.2C. The results are as follows Figure 4 As shown in , the initial capacity of S-LFP is 37.74 mAh / g.
[0047] Example 4
[0048] The repaired lithium iron phosphate positive electrode material powder obtained in Example 2 was mixed with a conductive agent (SuperP) and a binder (PVDF) in a ratio of 8:1:1 and ground for 30 minutes, then N-methylpyrrolidone (NMP) solution was added and continued to grind to form a uniform slurry, and then the mixed slurry was scraped on an aluminum foil and dried in an oven at 80°C for 12 hours to obtain CALi-LFP to prepare a positive electrode sheet. Then, CALi-LFP was used as the positive electrode, lithium foil as the negative electrode, and PP film as the separator to assemble button batteries. 20 μL of electrolyte was dripped on both sides of the positive and negative electrodes, and the assembled battery was left to stand for 8 hours before electrochemical testing.
[0049] The test was carried out at a charge and discharge rate of 0.2C. The results are as follows Figure 4 As shown in , the initial capacity of CALi-LFP is 135.35 mAh / g.
[0050] Example 5
[0051] The waste lithium iron phosphate positive electrode powder and lithium carbonate obtained in Example 1 were weighed and dispersed into deionized water according to Li:Fe:P=1.04:1:1, and the deionized water was evaporated to obtain a uniformly dispersed powder. The dried powder was heated to 750°C at a heating rate of 5°C / min in an atmosphere of 95% argon / 5% hydrogen, and kept warm for 10 hours to obtain lithium iron phosphate material LiCO3-LFP repaired with different lithium salts as a comparative sample.
[0052] Example 6
[0053] The lithium iron phosphate material LiCO3-LFP powder repaired with different lithium salts obtained in Example 5 was mixed with a conductive agent (Super P) and a binder (PVDF) in a ratio of 8:1:1 and ground for 30 minutes, and then N-methylpyrrolidone (NMP) solution was added and continued to grind to form a uniform slurry, and then the mixed slurry was scraped on an aluminum foil and dried in an oven at 80°C for 12 hours to obtain LiCO3-LFP to prepare a positive electrode sheet. Then, LiCO3-LFP was used as the positive electrode, lithium foil as the negative electrode, and PP film as the diaphragm to assemble button batteries. 20μL of electrolyte was dripped on both sides of the positive and negative electrodes, and the assembled battery was left to stand for 8h before electrochemical testing.
[0054] The test was carried out at a charge and discharge rate of 0.2C. The results are as follows Figure 4 As shown in , the initial capacity of LiCO3-LFP is 106.17 mAh / g.
[0055] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0056] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for repairing the positive electrode of a leaking waste lithium iron phosphate power battery, characterized in that: The following steps are involved: (1) Place the leaky waste lithium iron phosphate power battery in a salt solution and allow it to stand for deep discharge; (2) disassembling the discharged battery to obtain a discarded lithium iron phosphate positive electrode sheet, a separator and a discarded graphite negative electrode; (3) soaking the obtained waste lithium iron phosphate pole piece in dimethyl carbonate to remove residual electrolyte, and then drying to remove residual dimethyl carbonate to obtain a dried waste lithium iron phosphate pole piece; (4) subjecting the obtained waste lithium iron phosphate electrode to high temperature annealing to remove the binder and residual organic matter thereon; (5) separating the aluminum foil and the positive electrode powder from the lithium iron phosphate electrode after high temperature annealing, and obtaining the waste lithium iron phosphate positive electrode powder after separation; (6) dispersing the waste lithium iron phosphate positive electrode powder and the lithium citrate reagent into deionized water, and evaporating the deionized water to obtain a uniformly dispersed powder; (7) The obtained powder is placed in a furnace and calcined to obtain a repaired lithium iron phosphate positive electrode.
2. A method for repairing the positive electrode of a leaking waste lithium iron phosphate power battery according to claim 1, characterized in that: The step (1) of standing in the salt solution is standing in a saturated sodium chloride solution for 24 hours.
3. A method for repairing the positive electrode of a leaking waste lithium iron phosphate power battery according to claim 1, characterized in that: The disassembly in step (2) is carried out in a glove box filled with argon.
4. A method for repairing the positive electrode of a leaking waste lithium iron phosphate power battery according to claim 1, characterized in that: The soaking time in step (3) is 12 hours; the drying is performed at 80° C. for 12 hours.
5. A method for repairing the positive electrode of a leaking waste lithium iron phosphate power battery according to claim 1, characterized in that: The high temperature annealing in step (4) is to increase the temperature to 500° C. at a heating rate of 5° C. / min in an argon atmosphere and keep the temperature for 5 hours.
6. A method for repairing the positive electrode of a leaking waste lithium iron phosphate power battery according to claim 1, characterized in that: The waste lithium iron phosphate positive electrode powder and lithium citrate reagent described in step (6) are weighed according to Li:Fe:P=1.04:1:
1.
7. A method for repairing the positive electrode of a leaking waste lithium iron phosphate power battery according to claim 1, characterized in that: The calcination in step (7) is to increase the temperature to 750°C at a heating rate of 5°C / min in an argon atmosphere and keep the temperature for 10 hours.
Citation Information
Patent Citations
Method for recovering and recycling waste positive electrode material during production process of lithium iron phosphate battery
CN106505273A
Regeneration method of waste lithium iron phosphate positive material
CN107634222A
Regeneration process of waste lithium iron phosphate battery cathode material
CN112599766A
Method for directly repairing retired lithium iron phosphate positive electrode material by using surface coating layer
CN117977037A
Direct repair method for waste lithium-ion battery ternary positive electrode material
WO2022166197A1
Cited By
Method for preparing lithium iron manganese phosphate positive electrode material by recycling waste lithium iron phosphate
CN121493922A
